A concepção de infância da abordagem de San Miniato/Itália, um estudo de caso na perspectiva da formação dos professores e do currículo aberto ao possível - Silva, Claudio Amaro da (2020)
This research aims to analyze how the training of teachers, from San Miniato's, in Italy, approach, is able to influence the construction of a childhood curriculum, which comprehend children as protagonists. Based on this assumption, a case study with qualitative analysis is carried out, with questionnaires and documental analysis, seeking to understand the training of teachers in order to promote new pedagogical practices for children aged 0 to 3 years, starting from training as a guiding element that allows to reflect on and to share the experiences offered to children and their families. In this sense, the training constitutes a dimension that guarantees teachers the continuous updating when accompanying the educational project, starting from the children's experiences, in their learning path under a childhood curriculum, which allows to raise hypotheses of different paths that lead children to child protagonism. The subjects surveyed were teachers at daycare centers in San Miniato/Italy, who presented the childhood education and curriculum in their narratives, allowing a view on the role of the teacher within the services, in the aspect of group planning at the time of training. The International Childhood Research and Documentation Center Glória Tognetti was the path of this research, to understand the creation of a space for the training of teachers not only for the region of San Miniato/Italy, but also for the region of Tuscany/Italy